1999
DOI: 10.1590/s1415-790x1999000100004
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades socioespaciais na mortalidade do adulto no Município de São Paulo

Abstract: O aumento da importância da mortalidade do adulto tem sido acompanhado de uma grande produção científica sobre o tema nos países centrais. Nestes estudos, as desigualdades sociais têm sido avaliadas. Nos países periféricos, apesar de também se observar o crescimento da sua importância, têm sido realizados poucos estudos, em especial no que se refere às desigualdades sociais na sua geração e distribuição. Este trabalho tem como objetivo a análise das desigualdades sociais na mortalidade do adulto no município d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
(16 reference statements)
3
10
0
3
Order By: Relevance
“…In the contemporary world, the issue of violence deserves to be analyzed from all possible perspectives. Furthermore, this is not a specificity for homicides, for other studies 3,4 have demonstrated the association between the unequal distribution of male adult mortality in São Paulo City is also associated to other causes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the contemporary world, the issue of violence deserves to be analyzed from all possible perspectives. Furthermore, this is not a specificity for homicides, for other studies 3,4 have demonstrated the association between the unequal distribution of male adult mortality in São Paulo City is also associated to other causes.…”
Section: Discussionmentioning
confidence: 78%
“…This indicator presents values lower than 10 in the great majority of countries. 3 According to data from the 2001 National Household Sample Survey, in Brazil, this ratio is 18.3, that is, the richest 10% of the population earn 18 times more than the poorest 40% of the population. The richest one per cent of the population accumulates almost the same amount of earnings as the poorest 50% of the population in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…[77][78][79][80][81][82][83][84] Therefore, homicides were more prevalent in marginalised, socially excluded suburban neighbourhoods. Likewise, Dunn et al found that theft, as well as armed robbery, were higher among individuals treated in public clinics than among those treated in private clinics.…”
Section: -75mentioning
confidence: 99%
“…To overcome these limitations, at least partially, scholars have examined mortality differentials at different geographic levels and according to the distribution of several aggregated socioeconomic variables, such as household income, Gross Domestic Product (GDP) per capita, literacy rates and varying other measures. These studies have confirmed that better social indicators, such as better literacy rates, increased urbanization or GDP per capita, are highly correlated with greater life expectancy (Wood & Carvalho, 1988; Duarte, Schneider, Paes-Sousa, Silva & Castillo-Salgado., 2002; Messias, 2003; Ishitani, Franco, Perpétuo & França, 2006; Drummond & Barros, 1999; Silva, Paim & Costa, 1999; Szwarcwald et al, 1999). …”
Section: Introductionmentioning
confidence: 99%